2018
DOI: 10.1007/s10853-018-2459-1
|View full text |Cite
|
Sign up to set email alerts
|

Recrystallization and grain growth of a nano/ultrafine structured austenitic stainless steel during annealing under high hydrostatic pressure

Abstract: The aim of this study was to investigate the effect of high hydrostatic pressure applied during annealing on the processes of recrystallization and grain growth in nanostructured austenitic stainless steel 316LVM. The nanostructures were obtained by profile rolling to a total strain of 3.4 and by high-pressure torsion to a total strain of 79. These processes resulted in microstructures consisting of nanotwins and nanograins, respectively. The deformed samples were annealed at 900°C for 10 min under atmospheric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The impact of annealing under a pressure of 0.1 MPa, 2 GPa, and 6 GPa at 900 °C for 10 min on grain size and shape has been previously described and analyzed and will not be discussed in detail in this paper . The main conclusion can be drawn that the pressure retards the grain growth which was 2.0, 1.35, and 0.58 μm for annealing pressures of 0.1 MPa, 2 GPa and 6 GPa, respectively.…”
Section: Resultsmentioning
confidence: 97%
“…The impact of annealing under a pressure of 0.1 MPa, 2 GPa, and 6 GPa at 900 °C for 10 min on grain size and shape has been previously described and analyzed and will not be discussed in detail in this paper . The main conclusion can be drawn that the pressure retards the grain growth which was 2.0, 1.35, and 0.58 μm for annealing pressures of 0.1 MPa, 2 GPa and 6 GPa, respectively.…”
Section: Resultsmentioning
confidence: 97%
“…While Azuma et al (2012) conducted their annealing experiments at 1 atm, we performed ours at a hydrostatic pressure of 20 MPa. In many materials, including stainless steel and magnesium oxide, studies have observed that both the grain growth rate and grain-boundary diffusion coefficient decreased at higher pressures when compared to lower-pressure conditions (e.g., Farver et al, 1994;Krawczynska et al, 2018). However, ice behaves differently at high-pressure conditions compared to most oxides.…”
Section: Grain Growth Of Pure Icementioning
confidence: 99%